Analysis of the Phrase Iż Qāla and its Various Derivations in QS. Al-Baqarah - Ahmad Taqiyuddin Takdir; Muhammad Yusuf; Muhammad Yahya; Irfan Jaya Sakti; Alief Asyur Palallo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study examines the phrase īz qāla and its derivations in Surah Al-Baqarah. This phrase is commonly used as an introductory expression in important stories or events in the Qur’an, typically referring to Allah or His prophets delivering a message or teaching. The focus of this study is on the interpretation of how the phrase īz qāla and its various derivations appear in Surah Al-Baqarah. The researcher employed a library research methodology with a linguistic approach, leading to the finding that the phrase īz qāla and its various derivations in Surah Al-Baqarah all take the form of īz ẓarfiyyah. However, in this phrase, īz often indicates an event (maf’ūl bih) and carries a command to pay attention to the event described. The interpretation differs when īz qāla occurs in the middle of a verse, where there are various opinions regarding the meaning of īz in this context.